KEJADIAN ISPA PADA BALITA. APAKAH ASPEK IBU DAN BALITA BERPENGARUH? - Yulita, Hendra; Amin, Hadriyani; Mariani, Andi; Alfiah, Alfiah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Acute Respiratory Infections (ARI) are one of the leading causes of morbidity and mortality from infectious diseases worldwide. Based on a preliminary survey conducted by researchers in Sidangkal Village, South Padangsidimpuan District, it was found that the number of cases of Acute Respiratory Infections (ARI) in children has shown an increasing trend over the last three years. The purpose of this study was to determine the relationship between maternal and toddler factors and the incidence of ARI in toddlers. A cross-sectional study design was used in this study. The study was conducted in Sidangkal Village in August 2024. The population consisted of all mothers with toddlers in Sidangkal Village. The sample size was 8034 people. Probability sampling was used as the sampling technique. The research instrument used was a research questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed a relationship between maternal knowledge (p value: 0.038) and immunization status (p value: 0.040) and the incidence of ARI in infants. It is recommended that community health centers provide education through socialization or health counseling to the community so that they can increase their knowledge about ARI and the adverse effects of contracting ARI. Keywords: Toddlers, Immunization, Mother's Knowledge